An Investigation into the Antioxidant Effects of Frankincense Aqueous Extract and its Influence on Acetyl Cholinesterase in Alzheimer's patients in Diwaniyah - Meaad Nasser Hussein; Shaimaa Adnan; Ali Noory Fajer (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The present study aims to prepare the aqueous extract of the frankincense plant and then identify the most important biologically active substances in it, and study the effect of these substances against free radicals (2,2-diphenylpicrylhydrazyl (DPPH)) and Total Antioxidant Capacity. Then the effect of extract was tested on the blood serum of Alzheimer's patients in the nursing home in Diwaniyah Governorate, where 30 people were taken. 10 of them were healthy and were considered a positive control groupG1, and 20 of them were Alzheimer's patients, where 10 of them were considered a negative control groupG2, and the other 10 Alzheimer's patients had their serum treated with the extract of frankincenseG3. The effect of the extract on malondialdehyde and acetylcholinesterase enzyme was tested. The current study showed that extract contains biologically active substances such as (Flavonoids, Phenols, Tannins Triterpenoids, Steroids and Saponins) and these substances had an effective effect in inhibiting the radical (DPPH) where the inhibition rate reached 88% at (250mg/ml) and Total Antioxidant Capacity was (8.8*103 µmol/L) at the same concentration. That results also showed the significant rise in the concentration malonaldehyde in Alzheimer’s patients (G2, G3) when compared with G1. When the G3 was treated with the aqueous extract, a decrease in the concentration of malonaldehyde (3.23µml/l) was observed. The significant reduction in the Activity of the Acetylcholinesterase enzyme (3.97U/ml) was also observed in the (G3) as compared with(G2) (12.297U/ml). This is due to the biologically active substances in the extract, which indicates the possibility of using this extract to treat Alzheimer's patients in the future.